Answer:
0.8413 = 84.13% probability of a bulb lasting for at most 605 hours.
Step-by-step explanation:
Normal Probability Distribution:
Problems of normal distributions can be solved using the z-score formula.
In a set with mean
and standard deviation
, the z-score of a measure X is given by:
![Z = \frac{X - \mu}{\sigma}](https://tex.z-dn.net/?f=Z%20%3D%20%5Cfrac%7BX%20-%20%5Cmu%7D%7B%5Csigma%7D)
The Z-score measures how many standard deviations the measure is from the mean. After finding the Z-score, we look at the z-score table and find the p-value associated with this z-score. This p-value is the probability that the value of the measure is smaller than X, that is, the percentile of X. Subtracting 1 by the p-value, we get the probability that the value of the measure is greater than X.
The standard deviation of the lifetime is 15 hours and the mean lifetime of a bulb is 590 hours.
This means that ![\sigma = 15, \mu = 590](https://tex.z-dn.net/?f=%5Csigma%20%3D%2015%2C%20%5Cmu%20%3D%20590)
Find the probability of a bulb lasting for at most 605 hours.
This is the pvalue of Z when X = 605. So
![Z = \frac{X - \mu}{\sigma}](https://tex.z-dn.net/?f=Z%20%3D%20%5Cfrac%7BX%20-%20%5Cmu%7D%7B%5Csigma%7D)
![Z = \frac{605 - 590}{15}](https://tex.z-dn.net/?f=Z%20%3D%20%5Cfrac%7B605%20-%20590%7D%7B15%7D)
![Z = 1](https://tex.z-dn.net/?f=Z%20%3D%201)
has a pvalue of 0.8413
0.8413 = 84.13% probability of a bulb lasting for at most 605 hours.
Match of the equation with the verbal description of the surface would be :
Equation 1 = C. plane
Equation 2 = F. Circular cylinder
Equation 3 = C. plane
Equation 4 = E. sphere
Equation 5 = A. cone
Equation 6 = E. Sphere
Equation 7 = F. Circular cylinder
Equation 8 = B. Eliptic or circular paraboloid
Equation 9 = A. cone
Hope this helps
The answer would be 16 because 24 divided by 3 is 8. 8 multiplied by 2 is 16. 16 students have brown hair.
Answer:
<h2>
y = 2x + 6</h2>
Step-by-step explanation:
![M=\dfrac{y_2-y_1}{x_2-x_1}=\dfrac{2-0}{-2-(-3)}=\dfrac21=2](https://tex.z-dn.net/?f=M%3D%5Cdfrac%7By_2-y_1%7D%7Bx_2-x_1%7D%3D%5Cdfrac%7B2-0%7D%7B-2-%28-3%29%7D%3D%5Cdfrac21%3D2)
y = 2x + b passes through point (-3, 0), so:
0 = 2(-3) + b
0 = -6 + b
b = 6
Therefore the equation: <u>y = 2x + 6</u>